Pengaruh Penggunaan Learnıng Management System terhadap Efektıvıtas Pembelajaran Mahasıswa Fakultas Keguruan dan Ilmu Pendıdıkan Unıversıtas Papua - Engelbertus William Archian Nuhuyanan; Sri Wahyu Widyaningsih; Kaleb A. Yenusi; Irfan Yusuf (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
This study aims to determine the effect of convenience, usefulness, and service quality on the desire of FKIP UNIPA students to use LMS, and to determine the effect of the desire to use LMS on the learning effectiveness of FKIP UNIPA students. The research method used is the method of causality (cause and effect) in which the questionnaire is the research instrument. The sampling technique is using purposive sampling with a sample of 140 students. This study uses data analysis techniques, namely using t test using a linear regression model. The results of the analysis there are 2 models which can be seen in model I the significance value of the variable (X1) is 0.257, it can be said that this variable has no effect on (Z) because it is greater than 0.05, the variable (X2) is less than 0.001 it can be said that the variable this has an effect on (Z) because it is smaller than 0.05, and the variable (X3) is worth less than 0.001 it can be said that this variable has an influence on (Z) because it is smaller than 0.05, In model II it can be seen the significance value on the variable (Z) is less than 0.001 it can be said that this variable has an influence on (Y) because it is smaller than 0.05. This shows that in model I, in terms of usability and service quality, it can affect the desire to use LMS, while in terms of convenience it has no effect on the use of LMS, and for model II, it can be said that the desire to use LMS significantly affects learning effectiveness.